2020
DOI: 10.1111/ejh.13483
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of variant allele frequency (VAF) in TP53 mutant patients with MDS: A systematic review and meta‐analysis

Abstract: Tumor protein p53 (TP53) is frequently expressed in patients with myelodysplastic syndromes (MDS). Studies have already reported the poor prognostic impact of TP53 gene mutations in MDS patients. However, parts of this subgroup of patients with low-risk MDS still have relatively better survival and longer remission times. Therefore, we performed a meta-analysis to evaluate the prognostic difference intragene of variant allele frequency (VAF). The primary endpoint was overall survival (OS), and event-free survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…In contrast, in AML patients treated non-intensively with the hypomethylating drug azacitidine, an increasing mutant TP53 load was associated with a significantly increased risk for treatment failure [ 34 ]. A systematic review and meta-analysis of studies of patients with MDS also reported a high TP53 VAF as an independent prognostic parameter for survival with a 40% VAF as cutoff for high and low clonal burdens [ 35 ]. Recently, a report focusing on large cohorts of patients with MDS implemented the “ TP53 allelic state” as an important biological and clinical parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in AML patients treated non-intensively with the hypomethylating drug azacitidine, an increasing mutant TP53 load was associated with a significantly increased risk for treatment failure [ 34 ]. A systematic review and meta-analysis of studies of patients with MDS also reported a high TP53 VAF as an independent prognostic parameter for survival with a 40% VAF as cutoff for high and low clonal burdens [ 35 ]. Recently, a report focusing on large cohorts of patients with MDS implemented the “ TP53 allelic state” as an important biological and clinical parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, due to the high VAF, the UBA1 pathogenic variant in our case was misinterpreted as being in a hemizygous state. High VAF has been described in the literature to occur in postzygotic event such as clonal hematopoiesis in variants in TP53 with median VAF of 67.7% (range 46.9–84.7%) [ 17 ]. Regarding VEXAS, the highest value described in the literature was 83.35% in a patient diagnosed after analysis of peripheral-blood ES data [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of lenalidomide in MDS patients with isolated del(5q) harboring TP53 mutations is at a high risk of treatment failure and disease progression; this heterogeneity caused by TP53 mutations may significantly affect clinical decision making for MDS-del(5q) [ 56 ]. The genomic instability caused by TP53 inactivation was considered the pivotal reason for the accumulated chromosomal rearrangements [ 38 , 57 ], and the karyotype complexity is highly related to the variant allele frequency (VAF) of TP53 [ 58 ], which is an independent adverse prognostic factor for OS in MDS patients with TP53 mutations [ 59 ].…”
Section: Tp53 Mutation Features Within Mdsmentioning
confidence: 99%